2020
DOI: 10.1038/s41598-020-69401-4
|View full text |Cite
|
Sign up to set email alerts
|

Gene products and processes contributing to lanthanide homeostasis and methanol metabolism in Methylorubrum extorquens AM1

Abstract: Lanthanide elements have been recently recognized as “new life metals” yet much remains unknown regarding lanthanide acquisition and homeostasis. In Methylorubrum extorquens AM1, the periplasmic lanthanide-dependent methanol dehydrogenase XoxF1 produces formaldehyde, which is lethal if allowed to accumulate . This property enabled a transposon mutagenesis study and growth studies to confirm novel gene products required for XoxF1 function. The identified genes encod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 75 publications
6
67
1
Order By: Relevance
“…Our RNAseqbased gene expression analysis made use of the fitness-increase upon lanthanide supplementation under heterotrophic growth conditions with pyruvate as carbon source. The observed, slight downregulation of the genes coding for homologs of the TonB-ABC transport system was in line with previous reports in M. extorquens AM1 and Methylotuvimicrobium buryatense 5GB1C that observed a down-regulation of this machinery in response to excess lanthanides (20,52). Similar observations are known from iron homeostasis (53,54).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our RNAseqbased gene expression analysis made use of the fitness-increase upon lanthanide supplementation under heterotrophic growth conditions with pyruvate as carbon source. The observed, slight downregulation of the genes coding for homologs of the TonB-ABC transport system was in line with previous reports in M. extorquens AM1 and Methylotuvimicrobium buryatense 5GB1C that observed a down-regulation of this machinery in response to excess lanthanides (20,52). Similar observations are known from iron homeostasis (53,54).…”
Section: Discussionsupporting
confidence: 92%
“…The involvement of TonB-dependent receptors makes it likely that lanthanide uptake is linked to extracellular chelators similar to what is known for iron and copper uptake (17). Lanthanides are stored intracellularly in M. extorquens AM1 in mineral form (20). The widespread occurrence of lanthanide-dependent enzymes in (non-)methyotrophic organisms implies that multiple mechanisms for sensing, uptake, and on May 9, 2021 by guest http://aem.asm.org/ Downloaded from storing lanthanides exist in organisms that harness these metals for their metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lanmodulin seems not to be encoded in the MAG. Other studies indicated that TonB-dependent transporters might be involved in REE transport over the outer membrane, which are encoded by tonB or cirA genes (Ochsner et al 2019;Roszczenko-Jasińska et al 2020). The draft genome of ''Ca.…”
Section: Methanotrophymentioning
confidence: 99%
“…M. fumariolicum SolV grows optimally in acidic conditions (pH 2-5) making Ln 3+ soluble for uptake and utilization, and as such does not have a known dedicated transport system for these metals. In contrast, methylotrophs that grow at neutral pH have an ABC transport system and specific TonB-dependent receptor encoded in a "lanthanide-utilization and transport" gene cluster (Roszczenko-Jasińska et al 2020;Ochsner et al 2019). Of such organisms known to date, only a genetically manipulated mutant strain of Methylotenera mobilis JLW8 has been reported to show indications of growth with Gd 3+ in the form of increased culture density (Huang, Yu, and Chistoserdova 2018).…”
Section: Introductionmentioning
confidence: 99%